A study on the blended learning effects on students majoring in preschool education in the post-pandemic era: An example of a research-method course in a Chinese university - Nong, Weiguaju; Ye, Jian-Hong; Chen, Pengfei; Lee, Yi-Sang (Frontiers in Psychology, 2023)
The world has gradually entered the post-pandemic era. Although the pandemic has been slowing down, it still has a strong impact on the education scene. Thus, how to provide students with an effective and flexible learning style is currently an important educational issue. This study focused on the implementation of effective teaching to improve the learning effects based on these special circumstances. To ensure a realistic teaching situation, an experiment of blended teaching was conducted in a university in the Guangxi Zhuang Autonomous Region of China for a short-term study, based on the consideration of pandemic supervision and control. In this experiment, a single-group quasi-experimental design method, using the extended O-PIRTATD/S model, was adopted in a research-method course designed for students majoring in preschool education. This research-method course was an 8-week flipped course, where the first 4 weeks were online teaching and the last 4 weeks were taught offline, thus combining as a blended teaching course. A total of 115 active participants were recruited for this study. Based on the theoretical framework of the belief-action-outcome (BAO) model, five research hypotheses were proposed with the aim of constructing a learning behavior pattern based on cognitive beliefs which could be verified by structural equation modeling. The results of the study were concluded as follows: 1. Academic self-efficacy had a positive impact on learning engagement, but had a negative impact on cognitive load; 2. Cognitive load did not have a significant impact on learning engagement; 3. Learning engagement had a positive impact on the enhancement of academic self-confidence; and 4. Cognitive load had a negative impact on the enhancement of academic self-confidence.